Analisis Literasi Teknologi Informasi dan Komunikasi (TIK) Aparatur Sipil Negara Pemerintah Kabupaten Minahasa Tenggara - Andi, Fitria; Karouw, Stanley D.S.; Punuhsingon, Charles Punuhsingon S.C. (Universitas Sam Ratulangi, 2020)
Abstract - ICT has developed rapidly and needs to be mastered in this era, which is needed by everyone. Especially for the government, which in this case is the State Civil Apparatus as a performance support. Knowledge of ICT literacy is one important factor to support government performance. But in reality there are still many weaknesses found in ICT literacy in the State Civil Apparatus. The title of this study is